1990
DOI: 10.1177/38.7.2355174
|View full text |Cite
|
Sign up to set email alerts
|

Localization of metallothionein in the genital organs of the male rat.

Abstract: We studied the immunohistological localization of metallothionein (MT), a low molecular weight metal binding protein, in male rat genital organs (testis, epididymis, ejaculatory duct, seminal vesicle, coagulating gland, and prostate) by use of the avidin-biotin-peroxidase complex method. MT concentrations in testis, seminal vesicle, and prostate ranged from 15-30 micrograms/g tissue. In testis, seminiferous tubules with mature spermatozoa exhibited weak MT staining, whereas the tubules containing differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
42
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 23 publications
6
42
0
Order By: Relevance
“…MT was identified in human, rat, and rabbit prostate (2,10,13,14), and in the testis of rat and mouse (3,8). In the human prostate, MT concentration was the highest in the peripheral zone of normal prostate gland; MT was secreted from the prostatic epithelial cells into the prostatic fluids, which form a part of the seminal fluids, and it has been suggested that MT interacts with the sperm (10,11).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…MT was identified in human, rat, and rabbit prostate (2,10,13,14), and in the testis of rat and mouse (3,8). In the human prostate, MT concentration was the highest in the peripheral zone of normal prostate gland; MT was secreted from the prostatic epithelial cells into the prostatic fluids, which form a part of the seminal fluids, and it has been suggested that MT interacts with the sperm (10,11).…”
Section: Discussionmentioning
confidence: 97%
“…In the human prostate, MT concentration was the highest in the peripheral zone of normal prostate gland; MT was secreted from the prostatic epithelial cells into the prostatic fluids, which form a part of the seminal fluids, and it has been suggested that MT interacts with the sperm (10,11). Using Northern blotting and in situ hybridization, the localization of MT mRNA in the testis was observed in the primary spermatocytes and round spermatids, but not in Sertoli cells, interstitial cells, or in tailed spermatozoa of mice the role of MT in the male reproductive tracts, especially the excretory ducts of the testis, has not been studied in detail (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nishimura et al (1990) reported that MT was localized in the nucleus of rat sperm in the testis by an immunohistochemical study. Also, the level of MT mRNA is maintained at a high level in the spermatid in the mouse, but that in the mature sperm cells it is low (De et al 1991).…”
Section: Discussionmentioning
confidence: 99%